2021
DOI: 10.26633/rpsp.2021.70
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of the Healthy Municipalities Strategy in Guatemala

Abstract: Objective. Evaluate the sustainability of the Healthy Municipalities strategy in Guatemala in order to have solid evidence to support decision-making. Methods. A concurrent mixed-methods study was carried out in five phases: 1) theoretical-conceptual (based on a narrative review of the literature on sustainability, dimensions and categories were proposed for evaluation); 2) empirical (four municipalities were selected for convenience and 29 semi-structured interviews and four focus groups were conducted with k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The embedded research studies in this supplement also reveal the critical importance of engaging communities and cultivating capacity to collaborate with other sectors to achieve health goals. Laureano-Eugenio et al reviewed Guatemala’s Healthy Municipalities strategy to improve its implementation; they documented potential for improvements in terms of promoting and strengthening social participation as well as insufficient investments in working on the social determinants of health ( 10 ). In another example, Sacoto et al studied an initiative focused on preventing non-communicable diseases in Ecuador; they found that insufficient institutionalization could limit the effort´s sustainability and that the initiative needs to improve its coordination with other sectors and actors ( 11 ).…”
mentioning
confidence: 99%
“…The embedded research studies in this supplement also reveal the critical importance of engaging communities and cultivating capacity to collaborate with other sectors to achieve health goals. Laureano-Eugenio et al reviewed Guatemala’s Healthy Municipalities strategy to improve its implementation; they documented potential for improvements in terms of promoting and strengthening social participation as well as insufficient investments in working on the social determinants of health ( 10 ). In another example, Sacoto et al studied an initiative focused on preventing non-communicable diseases in Ecuador; they found that insufficient institutionalization could limit the effort´s sustainability and that the initiative needs to improve its coordination with other sectors and actors ( 11 ).…”
mentioning
confidence: 99%
“…Los estudios sobre la incorporación de la investigación que se presentan en este suplemento también muestran la importancia fundamental de fomentar la participación de las comunidades y cultivar la capacidad de colaborar con otros sectores a fin de alcanzar los objetivos buscados en el ámbito de la salud. Laureano-Eugenio et al, al examinar la estrategia de Municipios Saludables de Guatemala para mejorar su ejecución, documentaron el potencial de mejorar en la promoción y el fortalecimiento de la participación social, así como la insuficiencia de las inversiones en la labor relacionada con los determinantes sociales de la salud ( 10 ). En otro ejemplo, Sacoto et al estudiaron una iniciativa para prevenir enfermedades no transmisibles en Ecuador y observaron que una institucionalización insuficiente podría limitar la sostenibilidad del esfuerzo y que era necesario mejorar la coordinación de la iniciativa con otros sectores y actores ( 11 ).…”
unclassified
“…promoting and strengthening social participation as well as insufficient investments in working on the social determinants of health (10). In another example, Sacoto et al studied an initiative focused on preventing non-communicable diseases in Ecuador; they found that insufficient institutionalization could limit the effort´s sustainability and that the initiative needs to improve its coordination with other sectors and actors (11).…”
mentioning
confidence: 99%